Preparation of Fucoidan-Chitosan Hydrogel and Its Application as Burn Healing Accelerator on Rabbits - SEZER, ALİ DEMİR (PHARMACEUTICAL SOC JAPAN, 2008)
Treatment of dermal wounds with macromolecular agents such as natural polymers is one of the research areas of the biomaterial science. Fucoidan is a sulphated polysaccharide which is commonly obtained from seaweeds. The great number of studies on the different pharmacological properties of fucoidan is present, but there is limited information about using of fucoidan in the treatment of dermal burns. The aim of this study was to prepare fucoidan-chitosan hydrogels and to investigate their treatment efficiency on dermal burns. Hydrogels were prepared by swelling the polymers in acidic solution and their swelling, mechanical (hardness, cohesiveness and adhesiveness) and bioadhesive properties were investigated. The viscosity and water absorption capacity of formulations increased with increase in the polymer concentration. In contrast to the cohesiveness results, the adhesiveness of hydrogels increased with the polymer concentration. The bioadhesion was changed between 0.012-0.142 mJ.cm(-2) and enhanced with addition of fucoidan into gel formulations. It was formed dermal burns on seven adult male New Zealand white rabbits and the optimum gel formulation applied on the wounds. Control and treatment group biopsy samples were taken on days 7, 14 and 21 and each burn wound site was evaluated histopathollogically. No edema was seen in tested groups except control after 3 d treatment. After 7 of treatment, fibroplasia and scar were fixed on wounds treated with fucoidan-chitosan gel and fucoidan solution. The best regeneration on dermal papillary formation and the fastest closure of the wounds were observed in fucoidan-chitosan hydrogels after 14 d treatment.
Keywords: fucoidan chitosan; burn healing; hydrogel; bioadhesion; texture analyzer; MUCOADHESIVE PROPERTIES; FORMULATIONS; PH; POLYSACCHARIDES; MODULATION; GEL